The Megalonychidae (Xenarthra, Tardigrada) from the late Miocene of Entre Ríos Province, Argentina, with remarks on their systematics and biogeography - Brandoni, Diego (2011)
Megalonychidae are known from the Deseadan of Argentina and Bolivia to the present, represented by the tree sloth Choloepus Illiger. The principal fossil records of this clade are those from the Quaternary of Central America and the Antilles (e.g., Megalocnus Leidy, Acratocnus Anthony) and North America (e.g., Megalonyx Harlan, Pliometanastes Hirschfeld and Webb). From the Quaternary of South America, Megalonychidae are recorded in Peru (Diabolotherium Pujos, De Iuliis, Argot and Werdelin) and Brazil (e.g., Ahytherium Cartelle, De Iuliis and Pujos, Australonyx De Iuliis, Pujos and Cartelle). In Argentina they also have been recorded in the Santa Cruz Formation (early-middle Miocene) on the coast of Santa Cruz Province (Eucholaeops Ameghino), Arroyo Chasicó Formation (Protomegalonyx Kraglievich), Río Negro Formation, in the " conglomerado osífero" (ossiferous conglomerate) or " Mesopotamiense" (late Miocene) at the base of Ituzaingó Formation, Entre Ríos Province, and Pleistocene of Buenos Aires Province. Several authors have studied the Megalonychidae from the " conglomerado osífero", but no systematic revision of the group has been undertaken beyond the original naming of species. Taking into account that a broad range of individual variation has been observed in the Megalonychidae from the Pleistocene of North America and the West Indies, and that a similar range probably existed among the megalonychids from the " conglomerado osífero", then the number of valid species might be lower than previously proposed. Thus, the valid species recovered from the " conglomerado osífero" are Ortotherium laticurvatum Ameghino, Pliomorphus mutilatus Ameghino, Amphiocnus paranense Kraglievich, Protomegalonyx doellojuradoi Kraglievich, Pr. Praecursor Kraglievich, Megalonychops primigenius Kraglievich, and Paranabradys vucetichae Scillato-Yané. However, the establishment of synonymies, as well as the generic and specific assignation of the specimens is not an easy task, due to the peculiar taphonomical context of this stratigraphic unit.